2015
DOI: 10.1186/s13059-015-0692-3
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell mRNA sequencing identifies subclonal heterogeneity in anti-cancer drug responses of lung adenocarcinoma cells

Abstract: BackgroundIntra-tumoral genetic and functional heterogeneity correlates with cancer clinical prognoses. However, the mechanisms by which intra-tumoral heterogeneity impacts therapeutic outcome remain poorly understood. RNA sequencing (RNA-seq) of single tumor cells can provide comprehensive information about gene expression and single-nucleotide variations in individual tumor cells, which may allow for the translation of heterogeneous tumor cell functional responses into customized anti-cancer treatments.Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
232
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 244 publications
(242 citation statements)
references
References 65 publications
(95 reference statements)
6
232
0
Order By: Relevance
“…This has clearly increased the tumour complexity over performing analysis on bulk tissue showing even deeper levels of intra-tumour heterogeneity in many cancer types (3)(4)(5)(6). Single cell analysis on CSCs in osteosarcoma has, to our knowledge, currently not been reported but could significantly help to understand the diversity of these cells.…”
Section: Cancer Stem Cells and Tumour Heterogeneity: What Do We Know mentioning
confidence: 99%
“…This has clearly increased the tumour complexity over performing analysis on bulk tissue showing even deeper levels of intra-tumour heterogeneity in many cancer types (3)(4)(5)(6). Single cell analysis on CSCs in osteosarcoma has, to our knowledge, currently not been reported but could significantly help to understand the diversity of these cells.…”
Section: Cancer Stem Cells and Tumour Heterogeneity: What Do We Know mentioning
confidence: 99%
“…B1-3, singlecell suspension of the peripheral blood "cloudy" interface layer for CTCs, which mainly are of solid tumors. B2, four popular methods for single (cancer) cell isolation: FACS, microfluidics systems, micromanipulation system, and LCM (27). C, single-cell sequencing.…”
Section: Single-cell Wes Versus Single-cell Wgsmentioning
confidence: 99%
“…By using single-cell RNASeq data, the authors revealed substantial similarity with primary ALL cells isolated from pediatric and adult patients at minimal residual disease (MRD) [32]. Using this later approach, Kim et al were able to demonstrate a candidate tumor cell subgroup associated with anti-cancer drug resistance in viable lung adenocarcinoma in PDTX [48]. Additionally, Nguyen LV et al have applied a DNA barcoding technology to track the clonal evolution of breast PDTX.…”
Section: Pdtx In Basic Cancer Research Modeling Tumor Heterogeneity Amentioning
confidence: 99%